Effects of Rapid Maxillary Expansion and Facemask Therapy on the Soft Tissue Profiles of Class III Patients at Different Growth Stages - Ozzeybek Can, Fatma Selen; Turkkahraman, Hakan (European Journal of Dentistry, 2019)
Objectives The aim of this study was to evaluate the effects of rapid maxillary expansion (RME) and facemask therapy on the soft tissue profiles of class III patients at different growth stages.Materials and Methods Forty-five subjects (23 females and 22 males) were divided into prepubertal, pubertal, and postpubertal groups. Bonded type RME appliances and Petit-type facemasks were fitted to each patient, and intraoral elastics were applied from the hooks of the RME appliance to the facemask.Statistical Analysis All measurements were statistically analyzed with SPSS version 18.0 (SPSS Inc., Chicago, IL, United States) for Windows. Repeated-measures of ANOVA and posthoc Tukey tests were used to compare the groups.Results The soft tissue nasion, pronasale, subnasale, soft tissue A point, and labrale superior landmarks were all displaced forward and downward, and the most dramatic changes were recorded in the pubertal group. The labrale inferior, soft tissue B point, soft tissue pogonion, and soft tissue menton landmarks moved backward and downward in all groups, and the greatest displacements were observed in the pubertal group.Conclusions The soft tissue profiles improved significantly and became more convex in all treatment groups. Although, the most favorable facial changes were observed in the pubertal growth stage, the treatments applied in the postpubertal stage also elicited significant changes and should thus be considered viable treatment options.
Keywords: facemask; esthetics; class III treatment; soft tissue; rapid maxillary expansion